Effects of multi-circular jet plates on the spray and flame characteristics of internal mixing air-assisted atomizer - Amirnordin, Shahrin Hisham (2020)
The mixing of fuel and air plays a major role in the spray and flame behaviour, hence, affects the combustion performance and emissions of the internal mixing air-assisted atomizers. This research aims to determine the effects of multi-circular jet (MCJ) plates on the spray behavior and flame characteristics of air assisted atomizers. The MCJ plates provide the primary air entrance into the mixing chamber. The plates are represented by P1, P2, and P3 characterized by the difference in the open area ratio at 17.8, 18.4 and 18.9 respectively. Additionally, P1, P4, and P5 are represented by the jet-hole angles at 0o, 30o and 45o. In the experiments, the spray and flame images of all plates are captured at equivalence ratios of 0.8 to 1.2 using a Digital Single Lens Reflect camera. The flame temperatures are measured using the infra-red imaging technique while the emissions, burning chamber and stack temperature are also recorded using an emission gas analyzer and K-type thermocouples respectively. Then the computational work is conducted by using ANSYS Fluent to visualize the impact of plate geometry on the internal fluid flow and spray structure. Further analysis using both experiments and simulations have been carried out in order to compare between the P5 configuration and swirl. Results show that a decrease in open area ratio and jet-hole angle increases the flame temperature up to 11.4% and 13.8% respectively. The inclined jet-hole also increases the velocity up to 47.7% and turbulence kinetic energy up to 62.4% in the mixing chamber. In comparison between MCJ plate (P5) and swirl, P5 produces 33.8% lower backpressure but produces higher flame temperature at 4.3%. The result indicates that the MCJ plates are more effective in controlling the spray and flame characteristics of the atomizer. The outcome of this work provides a deeper understanding on the relations of geometry and fuel-air mixing to the characteristics of the internal mixing air-assisted atomizer which will lead to the improvement of burner systems in the future.